2015
DOI: 10.1166/mex.2015.1261
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensionally macroporous, Si and N-incorporated graphene aerogels for gas adsorbents

Abstract: Three-dimensionally macroporous, Si and N-incorporated graphene aerogels (3D SN-rGOAs) are successfully fabricated through a self-assembly, vapor deposition of (3-aminopropyl)triethoxysilane (APTES), and thermal treatment for gas adsorption applications. As investigated by spectroscopic methods, the interaction between oxygen-containing groups of GO and APTES results in the uniform incorporation of Si and N atoms on the surface of 3D SN-rGOAs. The resulting SN-rGOAs are composed of the 3D interconnected macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…For instance, Sui et al [22] showed that CO 2 uptake was more than doubled from 0.93 to 2.45 mmol/g at 1000 mbar and 0 C upon steam activation of a three-dimensional porous graphene-based material. Yun et al [31], on the other hand, fabricated Si-and N-incorporated GAs through vapor deposition of (3-aminopropyl)triethoxysilane (APTES) and showed an increase in CO 2 uptake from 1.74 to 2.38 mmol/g at 10,000 mbar and 25 C upon the deposition of APTES. Sui et al [23] reported an enhancement in CO 2 uptake from 1.6 to 2.6 mmol/g at 1000 mbar and 0 C, when GA was doped with nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Sui et al [22] showed that CO 2 uptake was more than doubled from 0.93 to 2.45 mmol/g at 1000 mbar and 0 C upon steam activation of a three-dimensional porous graphene-based material. Yun et al [31], on the other hand, fabricated Si-and N-incorporated GAs through vapor deposition of (3-aminopropyl)triethoxysilane (APTES) and showed an increase in CO 2 uptake from 1.74 to 2.38 mmol/g at 10,000 mbar and 25 C upon the deposition of APTES. Sui et al [23] reported an enhancement in CO 2 uptake from 1.6 to 2.6 mmol/g at 1000 mbar and 0 C, when GA was doped with nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…It causes various mutagenesis being non soluble in physiological pH aqueous solution (e.g. graphene/CNTs) or because they cannot be handled …”
Section: Introductionmentioning
confidence: 99%